“Efectos de la fertilización nitrogenada en el secuestro de carbono de la biomasa aérea del cultivo de arroz (oryza sativa) bajo riego al trasplante en la E.E. “El porvenir”- INIA-Juan Guerra” - Flores Flores, Warren (2004)
The present work has as title "Effect of the fertilization nitrogenada in the kidnapping of carbon of the air biomass of the cultivation of rice (Oryza sativa) 1 go down watering to the transplant in the E. E. El Porvenir'' - INIA - Juan Guerra"; likewise With the objective of quantifying the content of carbon kidnapped in the tour development stages (vegetative and reproductive stage) of the cultivation of rice after the trasplante and to determine the effect of the fertilization nitrogenada in rice, in the kidnapping of carbon; it was carried out the present work, in the Experimental field of the National Program of lnvestigation of Com and Rice of the E. E. The Porvenir which is located in the Km 14,5 South Highway Femando Belaunde Terry", District of Juan Guerra, County and Region of San Martin; with an annual maximum Tº of 27 ºC, precipitation averages yearly of 1 206 mm anda relativa humidity of 79 %. The used design was at random of Complete Blocks (DBCA), with factorial arrangement of 4 x 4, with dose of fertilization vs time. This alone arrangement one carries out for the parameter of capture of carbon, then for the other parameters carried out to the crop, you uses a (DCA), The treatments were T1 (O Kg N.ha-1), T2 (120 Kg N.ha-1 ), T3 (140 Kg N.ha-1 ) and T4 (160 Kg N.ha-1), The results demonstrated that the half dose of nitrogen (120 Kg N.ha-1), it accumulated bigger quantity of carbon in their structure with a total of 6 259,60 Kg.ha-1 of carbon, comparatively with the doses (140 Kg N.ha-1 and 160 Kg. N.ha-1 ) that accumulated 5 257,30; and 5 322,80 Kg.ha·1 · of carbon respectively; likewise the treatment To (O Kg. N.ha-1), 3 103,90 Kg.ha-1 of carbon accumulated, indicating the but low dose. The economic analysis shows us that the treatment T 2 (120 Kg. N.ha-1 ), it has obtained a bigger net utility of SI. 234.67 new suns which represents a relationship benefits cost of 1,06; overcoming to the other treatments in study.